(untitled) (Research, Society and Development, 2021)
Objective: Discuss the use of hormone therapy and the effects of its administration in the treatment of breast cancer in female patients. Method: Integrative review, carried out in July 2020, in the Scopus, Web of Science and Virtual Health Library databases, using the search strategy: “breast cancer” [AND] “aromatase inhibitors”; “breast cancer” [AND] “fulvestranto”; “breast cancer” [AND] “tamoxifen”. Results: 23 articles were selected, grouped according to the therapy used. Fulvestranto (30.43% of the articles), was effective in postmenopausal and palliative care; aromatase inhibitors (56.52% of the articles), obtained efficacy in association with another medication and alone in primary and metastatic breast cancer; tamoxifen (47.82% of the articles), demonstrated positive results as an adjuvant. As for side effects, the three drugs had complications. It should also be noted that the profile of women varied in age (18 to 82 years) and physiological aspects (pre and post menopause) Final considerations: Hormone therapy plays an important role in the treatment of women with breast cancer. However, it is necessary to consider the individual characteristics of the patients, since adverse effects can be avoided when the hormone is well administered, significantly altering the patients’ quality of life.